2005
DOI: 10.1111/j.1365-2648.2004.03298.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing relationship between mental health nurses and psychiatrists in the United Kingdom

Abstract: Psychiatrists in the UK remain highly influential, despite the move from their traditional power base in hospitals. Changes in mental health care, such as new nurse prescribing powers and the loss of psychiatrists' control over admission of patients to hospital, will continue to change the relationship between mental health nursing and psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…(2005) found that Directors of Nursing considered psychiatrists to be generally positive about supplementary prescribing, even though they had concerns about their ability to be effective nurse mentors. Brimblecombe (2004) argued that the relationships between psychiatrists and nurses have undergone multiple changes over the last four decades and changed beyond recognition since the late 19th century (Nolan 1993). The power once vested in psychiatrists is now dispersed among other disciplines and agencies.…”
Section: Literaturementioning
confidence: 99%
“…(2005) found that Directors of Nursing considered psychiatrists to be generally positive about supplementary prescribing, even though they had concerns about their ability to be effective nurse mentors. Brimblecombe (2004) argued that the relationships between psychiatrists and nurses have undergone multiple changes over the last four decades and changed beyond recognition since the late 19th century (Nolan 1993). The power once vested in psychiatrists is now dispersed among other disciplines and agencies.…”
Section: Literaturementioning
confidence: 99%
“…The result is the ‘legitimate’ control of large groups of staff by a small group of people. In psychiatry, this controlling hierarchy also reinforces other unhealthy historical qualities that we find hard to leave behind, such as remnants of the total institution and a paternalistic value system (Goffman 1968; Brimblecombe 2005). In addition, there is the blame culture, Benson et al .…”
Section: Discussionmentioning
confidence: 96%
“…1997). It also reflected the reality that the nurses’ right to withdraw their labour was actually the only power they had in an autocratic system (Brimblecombe 2005b).…”
Section: Discussionmentioning
confidence: 99%